THE PULSATIONS OF RADIAL VELOCITIES AMPLITUDE OF V 474 MON - THE DELTA SCT TYPE STAR - Udovichenko, S. N.; Lysova, L. E.; Paramonova, O. P. (Одеські астрономічні публікації, 2017)
The variations of radial velocities amplitude of V474 Mon - the Delta Set type star have been determined from spectrograms obtained at the 6-m telescope. Lines of metals are measured. The curves of radial velosities show both primary and secondary period variations, and a pulsation amplitude varies with the secondary period. Using the observations published earlier, the relationship between the radial velocity amplitude and the phase of the secondary period was obtained. The constant gamma-velocity does not confirm a suggestion that the system is binary.